Comparing and Assessing Statistical Distance Metrics within the Christian Apostle Paul’s Letters - Luce Alessandra; Robertson Paul (Open Theology)
This study applies and compares different metrics and statistical methods to Paul’s letters and a variety of roughly contemporary texts also written in Greek. The primary objective is to elucidate the distinctions between several notable metrics and statistical methods of comparison to discern the relative impact of their application on our understanding of Paul’s letters vis-à-vis our comparanda. The secondary objective is to compare the findings from different statistical metrics in order to assess their relative merits as statistical tools for literary analysis. Such analysis extends to determining the statistical significance of different methods’ relative findings and extracting meaningful insights about each metric and method. We aim to determine which metrics are most accurate and provide the most useful information in comparing Paul’s letters to other types of literature such as Greco-Roman philosophy, formal oratory, and so-called Jewish apocalyptic literature. Such findings are especially salient when comparing these quantitative methods to qualitative conclusions from the biblical commentary traditions of literary analysis and comparison.